The Physical Factors Application in Rehabilitation Programs for Patients after Total Knee Replacement - Detelina B. Kulchitskaya; Anatoliy D. Fesyun; Alexander S. Samoilov; Svetlana N. Kolbakhova (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2022)
Total knee replacement (TKR) surgery has been performed in increasing number of patients in recent years. Postoperative complicationsoften occur despite the improvement of the technique for performing this surgical intervention. All of the above confirms the need forthe development and implementation of modern rehabilitation programs for patients after TKR.Aim. To substantiate scientifically the feasibility of the combined use of cryotherapy and electrical stimulation in patients after TKR.Material and methods. We examined 90 patients who were admitted 3 months after TKR and were randomized into 3 groups. In thefirst group - 30 subjects received electrical stimulation of the quadriceps muscles and carried out therapeutic exercises for a course of10 procedures. In the second group - 30 subjects received electrical stimulation of the quadriceps muscles and air cryotherapy, performedtherapeutic exercises for a course of 10 procedures. In the third group - 30 people were given physical therapy classes only.Results. From the standpoint of the ICF, it has been proven that the physical factors application in the complex treatment of the abovepatients' category contributes to the improvement of "b 710 - the function of joint mobility". This is confirmed by the operated jointfunction improvement according to the KSS scale, microcirculation state enhancement, and the decrease in pain syndrome accordingto the VAS. The mobility level advance was revealed when evaluating the effectiveness of the proposed rehabilitation programs in thedomain "d 450-walking" based on the ICF. When assessing the domain "d 5-self-service", the HAQ questionnaire data indicate an increasein the ability to perform most activities in everyday life. However, more statistically significant results were obtained in patients aftera course of quadriceps electrical stimulation, air cryotherapy and therapeutic exercises.